Alexey Slapovsky vs Fyodor Dostoyevsky, or Life Without Being - Avtukhovich, Tatiana (Literatūra, 2021)
The article examines the dialogue in A. Slapovsky’s works of the late 1990s–2000s with F. Dostoevsky. The article highlights forms and functions of this dialogue: the mention of the writer's name, the reinterpretation of his works perform the function of an ironic, often parodic, reflection on the changed status of the author, the nature of the readership, the perception of literature during a crisis of literary centrism; the value deformations occurring in society are emphasized with the help of a literary prism. “Dostoevsky's context” reflects the writer's reflection on his own work and allows us to judge the direction of Slapovsky's creative evolution.
Keywords: A. Slapovsky; F. M. Dostoevsky; dialogue; irony; polemic; autoreflexion